John the Physician's Therapeutics : a medical handbook in vernacular Greek - Zipser, Barbara. (Studies in Ancient Medicine, 2009)
The Therapeutics of John the Physician is a medical handbook from the thirteenth century, holding important new evidence on medicine as craft. Of particular interest is a vernacular version of the text, which also contains a commentary. Here, an unknown reviser vividly describes cases and medical procedures, a type of knowledge rarely encountered in scholarly texts. In the present volume, the Therapeutics is published for the first time, along with a translation and an introduction to the topic. Apart from insights into medical history, the text also yields a large quantity of new material on the medical terminology used in everyday language and brings to life the development from ancient to modern Greek. The editorial technique may be of interest to those working on digital humanities.